2005
DOI: 10.1080/10407780590948918
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Laminar Heat Transfer in a Curved Rectangular Duct with a Computational Fluid Dynamics Code

Abstract: Flow and convective heat transfer in a curved rectangular channel was modeled and the heat transfer coefficient assessed, using the FLUENT code. The conditions considered are representative of an application to solar collectors with heat pipes. A wide range of Reynolds and Dean numbers was considered, under laminar flow conditions. Results show that the Nusselt number for the curved duct is up to 10 times higher than for a straight duct, due to counterrotating secondary vortices formation. The flow pattern cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It is one of the most widely used commercial codes for simulating engineering fluid flow and heat transfer problems due to its accuracy, robustness and convenience [18][19][20]. It uses a control-volume-based technique to convert the governing equations to algebraic equations that can be solved numerically.…”
Section: Methodsmentioning
confidence: 99%
“…It is one of the most widely used commercial codes for simulating engineering fluid flow and heat transfer problems due to its accuracy, robustness and convenience [18][19][20]. It uses a control-volume-based technique to convert the governing equations to algebraic equations that can be solved numerically.…”
Section: Methodsmentioning
confidence: 99%
“…A combined numerical and experimental study by Jiang et al [174] for flow through curved rectangular microchannel confirmed chaotic mixing to begin beyond a DN of around 100. The numerical study of Facao and Oliviera [188] revealed up to a ten-fold increase in Nu due to curvature of a rectangular channel along with splitting of the rolling pair to three vortex pairs at DN of 131. Similar investigations by Rosaguti et al [189][190][191] and Geyer et al [192] showed two and half to three times rise in Nu for flow of water through wavy microchannels depending on whether the flow section is circular, semi-circular or square.…”
Section: Channels With Converging-diverging Side Walls or Curved Axismentioning
confidence: 99%
“…Dolon et al [42] calculated heat transfer in the stable and oscillating flow behavior for the non-rotating curved duct of large aspect ratio. Facao and Oliveira [43] used the CFD method and fluent code to manipulate heat transfer in the rectangular duct for several Dean numbers. To the best of the authors' knowledge, the physical phenomena of the negative rotation through a curved duct is yet to understand.…”
Section: Introductionmentioning
confidence: 99%